Is there a temporal trend in the reported treatment efficacy of periodontal regeneration? A meta-analysis of randomizedcontrolled trials - Yu-Kang Tu (Blackwell Synergy, 2008)
Background/Aim: The aim of study was to conduct a meta-analysis to investigate whether or not there was a temporal trend in the treatment efficacy reported in the randomized-controlled trials (RCTs) on guided tissue regeneration (GTR) or enamel matrix protein derivatives (EMD) in the treatment of infrabony defects. Material and Methods: The treatment outcomes were changes in probing pocket depth (PPD) and clinical attachment level (CAL). Weighted multilevel and ordinary regression analyses were performed to test the temporal relationship between treatment effect difference or treatment effectiveness and publication years. Results: For PPD reduction, non-significant positive relationships were found in the treatment effect difference or treatment effect of both GTR and flap operation. For CAL gain, a small positive relationship was found in the treatment effect difference, but a significant positive trend in the treatment effect of flap operation was found. No significant temporal trend was found in the treatment effect difference for EMD. Conclusions: There was no evidence to support or refute a temporal trend in the treatment effect of regenerative procedures, but a positive trend was observed in the control group. These results suggest that only RCTs should be included in the meta-analysis, as the treatment effect of the control group may not be constant.